The impact of mobile money, remittances, and financial development on innovative growth in sub-Saharan Africa - Alhassan, Tijani F.; Guryanov, Sergey A.; Kouadio, Ahou J. (Economy of Regions, 2021)
Mobile money has become a mode of banking for the unbanked residents and the system has been gaining patronage among citizens of developing countries. This trend especially refers to sub-Saharan Africa, where the level of financial inclusion is low. Thus, the expansion of the mobile money as well as easy access to it promotes the development of the financial sector in the region. To define the role of the financial elements in innovation growth in sub-Saharan African countries, we examined the relationship between mobile money activities, remittance, financial development, and innovation growth in sub-Saharan Africa (SSA). Using partial least squares (PLS), we conducted a comprehensive analysis to econometrically establish the nexus between innovation development and financial activities in sub-Saharan African region. The results show that significant positive relationship exists between all the independent variables and innovation growth (the dependent variable). Thus, this study indicates that mobile money services, financial development and remittances have significant impact on economic growth. However, mobile money services are the most influential variable. Hence, these results can be used by policymakers to encourage and improve mobile money payment and banking system as this could facilitate the pooling of resources and their effective allocation to productive sectors, thus leading to the promotion of innovative growth in the region.